1995
DOI: 10.1038/375500a0
|View full text |Cite
|
Sign up to set email alerts
|

Glucosylation of Rho proteins by Clostridium difficile toxin B

Abstract: Toxin A and B, the major virulence factors of Clostridium difficile, are the causative agents of antibiotic-associated pseudomembranous colitis. In cultured cell lines their potent cytotoxicity results from their ability to induce disaggregation of the microfilament cytoskeleton. Toxin B acts on the low-molecular-mass GTPase RhoA, which is involved in the regulation of the actin cytoskeleton. We report here that toxin B catalyses the incorporation of up to one mole of glucose per mole of RhoA at the amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
836
1
3

Year Published

1997
1997
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 993 publications
(865 citation statements)
references
References 11 publications
14
836
1
3
Order By: Relevance
“…In fact, collagenolytic activity of SW620 cells was greatly diminished after Ad-RECK infection, as visualized by in situ zymography using DQ type I collagen (Figure 4c). We also found that the effect of type I collagen to downregulate SKP2 could be suppressed by the protein kinase C inhibitor GF109203X (Toullec et al, 1991) (Figure 4e) and the Rho-family GTPase inhibitor toxin B (Just et al, 1995) (Figure 4f), but not by the Src inhibitor PP2 (Hanke et al, 1996) (Figure 4d). Protein kinase C and Rhofamily GTPases are known to be involved in integrin signaling (Caswell et al, 2009).…”
Section: Reck Induces Skp2 Downregulation and P27 Upregulation In Sw6mentioning
confidence: 54%
“…In fact, collagenolytic activity of SW620 cells was greatly diminished after Ad-RECK infection, as visualized by in situ zymography using DQ type I collagen (Figure 4c). We also found that the effect of type I collagen to downregulate SKP2 could be suppressed by the protein kinase C inhibitor GF109203X (Toullec et al, 1991) (Figure 4e) and the Rho-family GTPase inhibitor toxin B (Just et al, 1995) (Figure 4f), but not by the Src inhibitor PP2 (Hanke et al, 1996) (Figure 4d). Protein kinase C and Rhofamily GTPases are known to be involved in integrin signaling (Caswell et al, 2009).…”
Section: Reck Induces Skp2 Downregulation and P27 Upregulation In Sw6mentioning
confidence: 54%
“…and Rho GTPase inhibitors, such as toxin B, 89 can inhibit macropinocytosis, they affect other endocytic pathways as well. Macropinosomes can acidify but do not intersect with lysosomes, 90 thus representing a potential alternative cell entry route of gene transfer for the avoidance of lysosomal degradation.…”
Section: Intracellular Trafficking Of Nonviral Vectors Lk Medina-kauwmentioning
confidence: 99%
“…Binding of ADP-ribosylated RhoA to GDI is increased, which leads to a cytosolic accumulation of inactive RhoRhoGDI complex ("trapping effect") Studies from recent years identified Rho GTPases as the preferred targets of several bacterial toxins. In addition to the ADP-ribosylation by C3, Rho GTPases are covalently modified by glucosylation (e.g., by clostridial glucosylating toxins; Aktories and Barbieri 2005;Just et al 1995b;Aktories and Just 2005;Voth and Ballard 2005;Just and Gerhard 2004), deamidation (e.g., by E. coli cytotoxic necrotizing factor; Schmidt et al 1997;Flatau et al 1997), and transglutamination (Bordetella dermonecrotizing factor; Masuda et al 2000) resulting in inactivation or activation of the GTPases respectively (Fig. 2).…”
Section: The Targets Of C3-like Exoenzymes Are Molecular Switchesmentioning
confidence: 99%